On nonlinear variational inequalities. (1991) - Noor, Muhammed Aslam
Abstract : The fixed point technique is used to prove the existence of a solution for a class of nonlinear variational inequalities related with odd order constrained boundary value problems and to suggest an iterative algorithm to compute the approximate solution.